2019
DOI: 10.1139/cjas-2016-0231
|View full text |Cite
|
Sign up to set email alerts
|

Performance, carcass characteristics, and centesimal composition of meat from Santa Inês lambs and Texel crossbred lambs (Santa Inês × Texel)

Abstract: This study evaluated the performance, carcass characteristics, and centesimal composition of the meat of intact and castrated lambs of the Santa Inês breed and of the crossbred animals: one-half Santa Inês × one-half Texel. Thirty-four lambs were used, nine intact and nine castrated males of the Santa Inês breed, and seven intact and nine castrated crossbred males, all aged between 6 and 7 mo and with an average live weight of 18.2 kg. The design was completely randomized in a 2 × 2 factorial (two crossing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
4
0
0
3
Order By: Relevance
“…In conformity with results of the current study, Nunes et al (2019) found that crossbreds with Texel had significantly higher carcass conformation scores than purebred lambs, while no difference was found in the fatness of carcasses between the considered genotypes. Nunes et al (2019) found no difference in rib eye muscle area nor leg width, while our research revealed that crossbreds with Texel had significantly larger rib eye muscles and wider legs than purebred JSR lambs. Scales et al (2010) studied the effect of commercial crossbreeding of Merino ewes with rams of several breeds (including Texel) on growth and carcass traits.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In conformity with results of the current study, Nunes et al (2019) found that crossbreds with Texel had significantly higher carcass conformation scores than purebred lambs, while no difference was found in the fatness of carcasses between the considered genotypes. Nunes et al (2019) found no difference in rib eye muscle area nor leg width, while our research revealed that crossbreds with Texel had significantly larger rib eye muscles and wider legs than purebred JSR lambs. Scales et al (2010) studied the effect of commercial crossbreeding of Merino ewes with rams of several breeds (including Texel) on growth and carcass traits.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the present study, they also found that Texel crossbreds had significantly higher daily gain than purebred Santa Ines lambs. As in the study of do Prado Paim et al 2013, Nunes et al (2019) did not report significant difference in hot and cold carcass weight nor in the dressing percentage between both genotypes, while in the present study crossbreds with Texel had significantly higher values for all the above-mentioned traits compared to purebred JSR lambs. In conformity with results of the current study, Nunes et al (2019) found that crossbreds with Texel had significantly higher carcass conformation scores than purebred lambs, while no difference was found in the fatness of carcasses between the considered genotypes.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Esto, levanta la hipótesis, si en la actualidad, es necesario el cruzamiento para la obtención de mejores resultados para las características de la canal y carne. Así mismo, aún faltan más estudios para la optimización de sistemas de producción existente y genotipos apropiados para la producción ovina en la región central de América del Sur (4). Por lo tanto, el objetivo del presente estudio fue evaluar las características cuantitativas de la canal y composición química de la carne de corderos puros Santa Inés y cruces con Dorper y Texel mediante un meta-análisis.…”
Section: /14unclassified